Improving teachers’ competence on the use of internet of things for teachers in the city of Makassar - Hala, Yusminah; Arifin, Arifah Novia (Journal of Community Service and Empowerment, 2020)
Internet of Things (IoT) is part of digital literacy that its function is undeniable when people are today obsessed more to social media and gadgets. IoT is greatly potential to support education field, especially in facilitating teachers. However, with all functions it has, IoT is not well mastered by many teachers in the city of Makassar. The issue is mainly because teachers are not well literate to IT. Therefore, it is significant to provide teachers with some trainings or workshops. Thus, this community service is projected to improve teachers’ competence in the use of IoT so that they will be life-long learners in the future. The ability to be life-long learner is one of the indicators to Sustainable Development Goals (SDGs). This community service has resulted in several outputs, they are: 1) teachers are equipped with the ability to use IoT and e-learning software, 2) the scoring results reveal that this community service has the average score of 4,67 (good criteria).